Anatomia ecológica do limbo foliar e de coléteres de espécies da tribo Coussareeae Benth & Hook. F. (Rubiaceae) - Gonçalves, Rhaniel Nicholas Lisowski, 1994- (2018)
Orientadores: Maria Fernanda Aguiar Calió, Juliana Lischka Sampaio Mayer